Impacts of a digital credit-insurance bundle for landless farmers: Evidence from a cluster randomized trial in Odisha, India - Kramer, Berber; Pattnaik, Subhransu; Ward, Patrick S.; Xu, Yingchen (Agricultural and Applied Economics Association, 2023)
Smallholder farmers often lack documented land rights to serve as collateral for formal loans, and their livelihoods are inextricably linked to increasingly variable weather conditions. Resulting credit and risk constraints prevent them from making potentially profitable investments in their farms. We implemented a randomized evaluation of the impacts of KhetScore, an innovative credit scoring methodology that uses digital technologies and in particular remote sensing to unlock credit and insurance for smallholders including landless farmers in Odisha, a state in eastern India. In our treatment group, where we offered loans and insurance based on the KhetScore methodology, farmers - and especially women - were more likely to purchase insurance, renew insurance coverage in subsequent years, and borrow from formal sources without substituting formal loans for informal loans. Despite increased borrowing, households in the treatment group faced less difficulty in repaying loans, suggesting that KhetScore loans, bundled with crop insurance, transferred risk and eased the burden of repayment. Moreover, the treatment increased agricultural revenues during the monsoon (kharif) season and reduced costs in the dry (rabi) season, enhancing profitability in both seasons. Positive and significant effects are found not only among baseline credit unconstrained farmers but also quantity rationed farmers, suggesting that KhetScore loans can help overcome supply-side credit constraints. Finally, women in the treatment group reported significantly higher levels of empowerment and mental health, manifested in increased participation in household decision-making and reduced feelings of stress, than women in the control group. In conclusion, digital technologies can contribute substantially to expansion in agricultural credit access, risk management, resilience, and well-being among marginalized landless farmers.